2012
DOI: 10.1016/j.neuron.2012.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Sensory Representations in the Olfactory Bulb: Modulation by Wakefulness and Experience

Abstract: SUMMARY How are sensory representations in the brain influenced by the state of an animal? Here we use chronic two-photon calcium imaging to explore how wakefulness and experience shape odor representations in the mouse olfactory bulb. Comparing the awake and anesthetized state, we show that wakefulness greatly enhances the activity of inhibitory granule cells and makes principal mitral cell odor responses more sparse and temporally dynamic. In awake mice, brief repeated odor experience leads to a gradual and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
286
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(356 citation statements)
references
References 68 publications
52
286
4
Order By: Relevance
“…Two to four weeks post-injection, we implanted a cranial window over the dorsal OB and investigated the Ca 2+ responses of GCs in anesthetized mice under baseline conditions and following odor stimulation ( Figures 1A and 1B). In line with and extending previous reports [6,23], our in vivo Ca 2+ imaging revealed the presence of functionally distinct subtypes of GCs based on their spontaneous activity. Slightly more than half of the GCs did not show any change in their fluorescence intensity during the 2-min acquisition period (30-Hz sampling rate; blue arrowhead in Figure 1C; top trace in Figure 1D).…”
Section: Functionally Heterogeneous Populations Of Gcs In the Adult Obsupporting
confidence: 91%
See 1 more Smart Citation
“…Two to four weeks post-injection, we implanted a cranial window over the dorsal OB and investigated the Ca 2+ responses of GCs in anesthetized mice under baseline conditions and following odor stimulation ( Figures 1A and 1B). In line with and extending previous reports [6,23], our in vivo Ca 2+ imaging revealed the presence of functionally distinct subtypes of GCs based on their spontaneous activity. Slightly more than half of the GCs did not show any change in their fluorescence intensity during the 2-min acquisition period (30-Hz sampling rate; blue arrowhead in Figure 1C; top trace in Figure 1D).…”
Section: Functionally Heterogeneous Populations Of Gcs In the Adult Obsupporting
confidence: 91%
“…Furthermore, it has previously been shown that GC activity increases with wakefulness [23]. We thus determined the percentage of CaMKIIa + GCs among all activated cells throughout the GCL and whether their activation differed in awake animals.…”
Section: Functionally Heterogeneous Populations Of Gcs In the Adult Obmentioning
confidence: 99%
“…First, we observed that the olfactory afterimage is state-dependent for it is both stronger and longer in awake mice than anesthetized mice. Whether this difference is due to top-down processes like attention or anesthesia-induced changes in the network (28,32) is impossible to disambiguate. We also observed that the olfactory afterimage is stronger in anesthetized mice for familiar odors over naïve odors although this effect was weak.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments performed so far were at a high odor concentration (5%), which evokes relatively dense activity patterns in glomeruli (28,32). To check whether olfactory afterimages are present at lower concentrations, and to see whether the afterimages contain concentration-specific information, we repeated our experiments using three lower odor concentrations (0.1%, 0.4%, and 2%).…”
Section: S2dmentioning
confidence: 99%
“…Unlike acute AOB slice experiments, which also expose circuit elements for electrophysiological and optical recordings, this preparation retains all sensory afferents and intra-AOB connections. Although this can also be said of anesthetized in vivo approaches, the presence of anesthetics necessarily alters neural function, namely excitatory/inhibitory balance, which is crucial for information processing in this and other olfactory circuits 18 . Because the preparation avoids the use of anesthetics, and because the AOB surface is completely exposed to the superfusate, it is amenable to pharmacological inquiries into local neural processing.…”
Section: Discussionmentioning
confidence: 99%